Demythologizing Celibacy: Practical Wisdom from Christian and Buddhist Monasticism - Funk, Mary Margaret (Cistercian studies quarterly, 2009)
The article reviews the book "Demythologizing Celibacy: Practical Wisdom From Christian & Buddhist Monasticism," by William Skudlarek.